Role of Water Hardness in Rinsing Bacteria from the Skin of Processed Broiler Chickens - Hinton. Jr., Arthur; Holser, Ronald (International Journal of Poultry Science, 2009)
The effect of water hardness on the ability of water to rinse bacteria from broiler skin was examined. Very hard water (total hardness = 200 ppm) was prepared by dissolving calcium chloride and magnesium chloride in distilled (soft) water and moderately hard water (total hardness = 100 ppm) was prepared by diluting 1 part very hard with 1 part soft water. After five consecutive rinses of skin in soft, moderately hard, or very hard water, samples were stomached in 0.01 M potassium phosphate buffer with 0.025% ethylenediaminetetraacetic acid to recover bacteria remaining on the skin. Bacteria in stomached rinsates were enumerated on Plate Count (PC), Levine Eosine Methylene Blue (EMB), Campylobacter (CA), Pseudomonas (PS) and Staphylococci (ST) Agars. Results indicated that significantly (p